2021
DOI: 10.3390/microorganisms9071486
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Weissella viridescens UCO-SMC3 as a Potential Probiotic for the Skin: Its Beneficial Role in the Pathogenesis of Acne Vulgaris

Abstract: Previously, we isolated lactic acid bacteria from the slime of the garden snail Helix aspersa Müller and selected Weissella viridescens UCO-SMC3 because of its ability to inhibit in vitro the growth of the skin-associated pathogen Cutibacterium acnes. The present study aimed to characterize the antimicrobial and immunomodulatory properties of W. viridescens UCO-SMC3 and to demonstrate its beneficial effect in the treatment of acne vulgaris. Our in vitro studies showed that the UCO-SMC3 strain resists adverse g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 76 publications
0
12
0
1
Order By: Relevance
“…This potential probiotic activity is supported by observations that some Weissella species can overcome the gastric barrier (Wang et al, 2008 ) and produce antimicrobial compounds such as bacteriocins (Srionnual et al, 2007 ; Masuda et al, 2012 ). For example, W. cibaria has been reported to inhibit biofilm formation in vitro and the proliferation of the main bacterial pathogens in dental caries and upper respiratory infections (Yeu et al, 2021 ), and has been studied for its potential anti-inflammatory activity against lipopolysaccharide stimulation (Yu et al, 2019 ), while W. viridescens was proposed as a potential probiotic for the skin (Espinoza-Monje et al, 2021 ). Furthermore, potential probiotic features of this genus include the reduction in depressive-like behavior (Sandes et al, 2020 ), the influence on gut permeability and intestinal epithelial regeneration (Prado et al, 2020 ), and the antagonistic activity against common human pathogens (Afolayan et al, 2017 ; Choi et al, 2018 ; Yu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This potential probiotic activity is supported by observations that some Weissella species can overcome the gastric barrier (Wang et al, 2008 ) and produce antimicrobial compounds such as bacteriocins (Srionnual et al, 2007 ; Masuda et al, 2012 ). For example, W. cibaria has been reported to inhibit biofilm formation in vitro and the proliferation of the main bacterial pathogens in dental caries and upper respiratory infections (Yeu et al, 2021 ), and has been studied for its potential anti-inflammatory activity against lipopolysaccharide stimulation (Yu et al, 2019 ), while W. viridescens was proposed as a potential probiotic for the skin (Espinoza-Monje et al, 2021 ). Furthermore, potential probiotic features of this genus include the reduction in depressive-like behavior (Sandes et al, 2020 ), the influence on gut permeability and intestinal epithelial regeneration (Prado et al, 2020 ), and the antagonistic activity against common human pathogens (Afolayan et al, 2017 ; Choi et al, 2018 ; Yu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro studies using the minimal inhibitory concentration assay showed Staphylococcus aureus ( S. aureus ) growth suppression, another potential pathogen related to AV 19,20 . On the contrary, Espinoza‐Monje et al proposed the emergence of the snail microbiota in snail slime, such as lactic‐acid producing bacteria, which may demonstrate C. acnes growth inhibition, resulting in a less inflammatory response 21 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a murine model, Weissella viridescens UCO-SMC3, both administered orally and topically, was shown to beneficially modulate the immune response against C. acnes and reduce C. acnes replication in lesions. Even orally, Weissella viridescens UCO-SMC3 produced a more potent anti-inflammatory response than topically [ 123 ].…”
Section: Acne Vulgaris and Probioticsmentioning
confidence: 99%